VIABILIDADE ECONÔMICA DA GERAÇÃO DE ENERGIA ELÉTRICA A PARTIR DO BIOGÁS GERADO EM ESTAÇÃO DE TRATAMENTO DE EFLUENTE INDUSTRIAL DE CERVEJARIAS - Silva, Adriana Ribeiro da (2014)
Several industrial wastewater treatment plants using biogas from anaerobic processes in plants as a source of fuel for generators of electricity. This biogas comprises mainly methane which results from the digestion of organic matter in bioreactors. Biogas as alternative energy source, can be a viable solution for two major global problems that comes with population growth: increasing energy consumption and increased production of solid, liquid and gaseous. The viability of such use depends directly on the capacity of each project. This work is an approach to the study of economic viability of biogas use generated in a brewery for conversion into electricity. All data collected were collected during the period from June 2013 to July 2014, in the company's information system. The biogas generated in ETEI a brewery for conversion to electricity was studied. As the deployment of value biogas reuse project, the cost reduction opportunity for brewing and demonstrated the economic viability of biogas reuse as electric power through more traditional financial indicators as payback (bp), net present value (NPV), internal rate of return (IRR), efficiency ratio and hurdle rate. Because the growth of drinking and consequently organic load in effluent generation, as we have great potential in this business the generation of biogas that can be converted into electrical energy using already dominated the market technology.